Ownership versus Shared Economy: Implications on German car manufacturers - Schneider, Maximilian Alexander (2020)
Purpose – In times of financial uncertainty, sustainable demands, and resource scarcity, consumers tend to share rather than own items. Digitalization has played its part, start-ups have evolved, and suddenly consumers become suppliers. This work will assess the implications of the shared economy and digitalization on the German automotive industry. Design/Methodology – The theoretical research exhausts vast literature and recent news to understand changing consumer preferences and the impact of digitalization on the automotive industry. By using a qualitative data collection approach, the academic findings are supported by practical insights, gained through eight conducted interviews. Findings – This dissertation concluded that the car has to become pre-dominantly a service rather than the actual hardware. Carmakers have to move towards becoming software companies to stay competitive with tech giants entering the field. Research limitations – The main limitation of this research is the actual consequences of COVID-19. Those implications are neglected in this dissertation. Practical implications – The derived results from this dissertation will support German carmakers in understanding and analyzing the changes in their environment. Social implications – By incorporating ecosystems and engaging in collaborations across industries, German OEMs can contribute to a more productive and efficient economy. Originality – To my knowledge, there is not yet sufficient research on the impact of the shared economy and digitalization on the German automotive industry.